A mobile phone application for the prevention of type 2 diabetes in Malaysian women with gestational diabetes mellitus (MYGODDESS): A feasibility randomised controlled trial - Benton, Madeleine; Goldsmith, Kimberley; Ching, Siew Mooi; Forbes, Angus; Nadal, Iliatha Papachristou; Murphy, Helen R.; Sobri, Nur Hafizah Mahamad; Yusof, Barakatun Nisak Mohd; Basri, Nurul Iftida; Ismail, Irmi Zarina; Ismail, Khalida; Chew, Boon How (John Wiley and Sons Inc, 2026)
Aims: The prevalence of gestational diabetes mellitus (GDM) in Malaysia is estimated at 9–18%. Although GDM is associated with increased and potentially modifiable risk of developing type 2 diabetes, the effectiveness of diabetes prevention interventions (DPI) post-GDM in this setting is unclear. To evaluate the feasibility of conducting a future full-scale, two-arm, parallel, randomised controlled trial (RCT) of a DPI in women with GDM set in Malaysia. Methods: Women in both arms received usual GDM care. Women in the intervention arm also received modules on diet, physical activity, and mental health via a mobile application, over six months post-partum, plus dietitian-led group sessions and motivational text messages. The primary feasibility outcomes included the proportion of women who consented, were eligible and randomised and provided outcome data. We measured biomedical and mental health outcomes for a full-scale RCT at four time points: baseline before randomisation (approximately 30 weeks' gestation), 36 weeks' gestation and 3- and 6-months postpartum. Results: We screened 660 women with GDM, 294 (45%) consented for eligibility screening, of whom 164 (24.9%) were eligible and 60 (9%) consented and were randomised. The proportion who completed biomedical outcomes was 85% at each follow-up. There was no treatment effect on any other biomedical outcomes or secondary outcomes. Conclusions: The participation rate was in keeping with previous DPI trials and the attrition rate was low, suggesting it is feasible to conduct a full-scale RCT.